Economic Analysis of Households and Education Levels of Parents on the Decision to Continue to College Education at SMK Siang, Tulungagung District - Nursalim Bayu Mu'arif; Narfik Umurul Hadi (INTERDISCIPLINARY JOURNAL ON LAW, SOCIAL SCIENCES AND HUMANITIES, 2020)
This research is motivated by the still low number of students who continue their studies to higher education in Tulungagung, Indonesia. This can be seen in the attitude of students who do not show interest in the compilation of high school choices presented by the teachers. The purpose of this article is threefold. First, this article aims to elucidate how the level of household economics is related to the decision to enroll in higher education. The second research objective is to find whether the parental level of education has an impact on the decision to continue in higher education. Third, this study aims to understand whether the combined influence of household economic level and parental level of education influences the decision of studying higher education. This paper relies on questionnaires conducted in the class X SMK SIANG Tulungagung during the academic year 2019/20 as a method of data collection. The data analysis techniques include validity, reliability, classic assumption tests, multiple linear regression and hypothesis testing. The results of the data analysis show that: (1) the value of t arithmetic in the variable (X1) ‘analysis of the household economic’ of 2.148 <t table are 2.004. Thus, it can be concluded that there are significant differences in how the household economic level influences the decision to go to college. (2) The value of t arithmetic on the variable (X2) ‘level of parental education’ of 2,200> t table is 2,006. College. (3) The test results obtained through calculating the F value of 4.970> from F table are 3.16. College.